Quantitation of the Action of Ethylenediaminetetraacetic Acid and Tris(hydroxymethyl)aminomethane on a Gram-Negative Bacterium by Vancomycin Adsorption - Haslam, Donald F. (1970)
Changes in the cell wall of a species of Flavobacterium can be quantitated by measuring vancomycin adsorption. Treatment of the cells with ethylenediaminetetraacetic acid or tris(hydroxymethyl)aminomethane (or both) increased adsorption of the antibiotic.